Effect of immobilisation on human forearm fuel metabolism - Burns, Aisling (2019)
Worldwide it has been estimated that physical inactivity causes between 6-10% of global deaths, with low physical activity levels directly linked to 25-27% of the incidence of type 2 diabetes, 21-25% of breast and colon cancers, and approximately 30% of ischaemic heart disease. Thus, elucidating the underlying mechanisms between physical inactivity and the associated negative implications for health is imperative to establish and implement effective countermeasures. Currently bed rest and limb immobilisation represent the most popular experimental models used to investigate the functional and metabolic perturbations associated with physical inactivity. Forearm immobilisation was employed in each of the studies presented in this thesis, a model which allows the contralateral, non-immobilised arm to act as a within volunteer control. Furthermore, upper limb immobilisation facilitates the exploration of the reduced muscle use without the confounding effects of decreasing overall levels of physical activity and has a decreased risk of deep vein thrombosis compared to lower limb immobilisation.